2020
DOI: 10.1016/j.cjca.2020.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Implications of the COVID-19 Pandemic: A Global Perspective

Abstract: The coronavirus disease 2019 , caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), represents the pandemic of the century, with approximately 3.5 million cases and 250,000 deaths worldwide as of May 2020. Although respiratory symptoms usually dominate the clinical presentation, COVID-19 is now known to also have potentially serious cardiovascular consequences, including myocardial injury, myocarditis, acute coronary syndromes, pulmonary embolism, stroke, arrhythmias, heart failure, and card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
155
0
27

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(193 citation statements)
references
References 82 publications
2
155
0
27
Order By: Relevance
“…Given the vast number of people living with prevalent vascular risk factors and the rapid global spread of the COVID-19 pandemic, it is essential to know how vascular risk factors influence the risk of developing severe COVID-19 disease. Most previous studies showed an association between vascular risk factors (such as hypertension and diabetes) and COVID-19 severity [7]. However, little is known about how patients stratified by burden of vascular risk factors differ from each other, and whether the number of vascular risk factors is associated with COVID-19 disease severity.…”
Section: Introductionmentioning
confidence: 99%
“…Given the vast number of people living with prevalent vascular risk factors and the rapid global spread of the COVID-19 pandemic, it is essential to know how vascular risk factors influence the risk of developing severe COVID-19 disease. Most previous studies showed an association between vascular risk factors (such as hypertension and diabetes) and COVID-19 severity [7]. However, little is known about how patients stratified by burden of vascular risk factors differ from each other, and whether the number of vascular risk factors is associated with COVID-19 disease severity.…”
Section: Introductionmentioning
confidence: 99%
“…Risk stratification methods such as Caprini, IMPROVE, Padua models, and VELTAS (Venous and Lymphatic Triage and Acuity Scale) are proven to be useful for clinical assessment of VTE and PE in COVID-19 [ 8 , 9 ]. Prophylactic anticoagulant therapy is recommended with LMWH or unfractionated heparin with or without mechanical compression [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…All patients had elevated D-dimer on presentation. One of the patients had new onset Ab with RVR after 7 days of respiratory symptoms with elevated troponin I, which could be a sequalae of COVID-19 related myocardial injury [16,17], illustrating exasperation of underlying conditions and COVID-19's prothrombotic state. COVID-19 related myocardial arrhythmia with elevated Troponin may be yet another potential etiology of ischemic stroke, independent from the hypercoagulable state.…”
Section: Discussionmentioning
confidence: 99%